(untitled) (Marketing Jurnali, 2026)
This article scientifically analyzed the role of small business and private entrepreneurship in promoting economic growth and employment in Uzbekistan. The study evaluated the contribution of small businesses to gross domestic product, exports, imports, and employment using official statistical data and reports from international organizations. It systematically examined access to finance, institutional reforms, credit guarantee mechanisms, entrepreneurship support policies, and regional development factors. The findings demonstrated that the expansion of small businesses contributed to strengthening economic stability, creating new employment opportunities, increasing export potential, and improving the competitiveness of the private sector. The proposed approach also provided a reliable scientific foundation for enhancing entrepreneurship support policies and fostering sustainable economic development.